Coordinated U.S. Foreign Assistance and Effective Counterterrorism in Africa: Considering the Efficacy of U.S. and Partner Engagement against Al Qaeda’s Civilian Engagement Strategy in West Africa - Palacios, Tammy (Journal of Central and Eastern European African Studies, 2025)
The international community can better partner with African countries and more effectively counter and prevent terrorism in Africa by implementing two changes to U.S. strategy. First, by crafting strategies that counter the kinetic and non-kinetic operations of al Qaeda and ISIS affiliated groups that allow for their territorial expansion and control. Second, by better coordinating U.S. foreign aid/development with security assistance and security cooperation efforts and conducting them with the partner country in a way that supports partner civilian and military institutions. At current, U.S. security assistance efforts better connect to and strengthen the military/security apparatus than U.S. development assistance efforts do - this is due to risk averse bureaucracy that ultimately erodes democratic structures and processes rather than strengthening them. Additionally, U.S. tendencies to work directly with civil society organizations may not strengthen civil society pathways to ministries or the relevant offices at the district or national levels. U.S. and other international partners should work through and support a hub where local civil society and local level authorities can engage with and work with the district and national level governments. This strategy will strengthen good governance and democratic institutions. Additionally, terrorism prevention and counterterrorism strategies that directly address and are formed in response to both active kinetic and non-kinetic operations of (al Qaeda and ISIS-affiliated) terrorist groups will better protect civilians as well as implementors of development and security assistance.